Nutrition Counseling Improves Diabetes Mellitus Knowledge among Prolanis Participants - Siti Uswatun Hasanah; Fitri Wahyuni; St. Masithah; Andi Rahmaniar MB (Sarana Ilmu Indonesia (salnesia), 2026)
Diabetes mellitus is a chronic disease that requires continuous management, including proper nutritional therapy. However, limited knowledge of diabetes and its dietary management remains a challenge among participants in the Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis; Prolanis). This community service activity aimed to improve Prolanis participants' knowledge of Diabetes mellitus through structured nutrition counseling. The program was conducted at Turikale Primary Health Center, Maros Regency, involving 25 Prolanis participants. Structured nutrition counseling was provided in three sessions over three weeks using leaflets as educational media. Program effectiveness was evaluated using a one-group pretest–posttest design. Participants' knowledge was assessed using a questionnaire before and after the intervention. Data were analyzed using the Paired Sample t-test. The results showed that the mean knowledge score increased from 54.97 ± 20.81 before the intervention to 77.00 ± 19.90 after the intervention, a mean increase of 22.03 points. Statistical analysis revealed a significant difference between pre-test and post-test scores (p = 0.001). Participants also demonstrated active participation throughout the counseling sessions. In conclusion, structured nutrition counseling effectively improved knowledge of Diabetes mellitus among Prolanis participants. This activity may serve as a practical and sustainable educational strategy to support diabetes management in primary healthcare settings.